Variability in ginger(Zingiber officinale rosc) for yield and resistance to rbizome rot - Anargha T (Department of plantation crops and spices, college of agriculture, 2019)
A field experiment entitled “Variability in ginger (Zingiber officinale Rosc.) for yield and resistance to rhizome rot” was conducted at Department of Plantation Crops and Spices, College of Agriculture, Vellayani during 2017-2019 with the objective to evaluate ginger genotypes for yield and resistance/tolerance to rhizome rot. The study on variability in ginger (Zingiber officinale Rosc.) for yield and resistance to rhizome rot was conducted as two experiments (i) Collection of ginger genotypes and analysis for genetic variability and yield (ii) Screening of ginger genotypes against rhizome rot under natural condition. Twenty genotypes of ginger collected from different regions of Kerala and a control variety Aswathy were planted in Instructional Farm, College of Agriculture, Vellayani in a randomized block design with four replications. Qualitative characterization of the genotypes was carried out based on DUS guidelines. Plant growth habit of collected genotypes included erect and semi-erect types. All the genotypes were short type (height<100cm) with short leaf length (<25cm), medium leaf width (2.5-3.5cm) having few (<10) and medium (10-15) shoots. The intensity of shoot colour noticed was green and dark green while that of leaf were light green, green and dark green. The leaf petiole length was short (<0.5cm) for all the genotypes except T17 (Kalliyur). Spikes were formed only in three genotypes of which two had crimson bract tip and other had yellowish white tip. Rhizome thickness was thin (<2cm) for all genotypes except T11 (Kazhakootam) with medium (2-3cm) thickness with straight, curved and zigzagged rhizome shape. Greyish yellow rhizome skin colour was predominant while the flesh colour were light yellowish grey, greyish yellow and yellow. The collected genotypes sprouted from 7 days after planting and continued upto 20 days after planting. Plant height was significantly superior for T12 (Irinjalakkuda) while the number of tillers and dry matter content was significantly higher for T11 (Kazhakootam) at 7 MAP. Leaf area for T8 (Karunagapally) was 48.2 cm2 which was